Long‐term outcomes of nasogastric tube with Gastrografin for adhesive small bowel obstruction. Issue 1 (21st September 2021) - Nishie, Hirotada; Shimura, Takaya; Katano, Takahito; Iwai, Tomohiro; Itoh, Keisuke; Ebi, Masahide; Mizuno, Yusuke; Togawa, Shozo; Shibata, Shunsuke; Yamada, Tomonori; Mizushima, Takashi; Inagaki, Yusuke; et al.
Abstract: Background: We had previously reported that the administration of Gastrografin through a nasogastric tube (NGT‐G) followed by long tube (LT) strategy could be a novel standard treatment for adhesive small bowel obstruction (ASBO); however, the long‐term outcomes after initial improvement remain unknown. This study aimed to analyze the long‐term outcomes of first‐line NGT‐G. Methods: Enrolled patients with ASBO were randomly assigned to receive LT or NGT‐G between July 2016 and November 2018. Thereafter, the cumulative surgery rate, cumulative recurrence rate, and overall survival (OS) rate were analyzed. In addition, subset analysis was conducted to determine the cumulative recurrence rate according to colonic contrast with Gastrografin at 24 h. Results: A total of 223 patients (LT group, n = 111; NGT‐G group, n = 112) were analyzed over a median follow‐up duration of 550 days. The cumulative 1‐year surgery rates, cumulative 1‐year recurrence rates, and 1‐year OS rates in the LT and NGT‐G groups were 18.8% and 18.1%, 30.0% and 31.7%, and 99.1% and 96.6%, respectively; no significant differences were observed between both groups. In the NGT‐G group, a negative colonic contrast at 24 h demonstrated a higher tendency for future recurrence compared with a positive colonic contrast at 24 h (1‐year recurrence rate: negative contrast, 46.9% vs positive contrast, 27.6%). Conclusions: Gastrografin through a nasogastric tube followed by LT can be a promising treatment strategy for ASBO, with long‐term efficacies equivalent to initial LT placement.